Evaluation of sleep quality among chemotherapy-treated cancer patients - Kustriyani, Menik; Prasetyorini, Heny (University of Muhammadiyah Semarang, 2024)
Cancer arises from a variety of diseases, injuries, benign tumors, lifestyle factors, and other issues. Approximately 50% of cancer patients experience sleep disturbances, such as insomnia and abnormal sleep cycles. This study aims to describe the sleep quality of cancer patients undergoing chemotherapy. Methodology: This quantitative research employs a descriptive approach, with consecutive sampling used to select participants. The sample consisted of 41 cooperative cancer patients undergoing chemotherapy who were capable of performing daily activities. Informed consent was obtained from respondents, and data were collected using the Pittsburgh Sleep Quality Index (PSQI) questionnaire. The results indicated that of the seven PSQI indicators, 54.4% of patients subjectively reported good sleep quality, 46.3% had a sleep duration of 5-6 hours, and 43.9% experienced a sleep latency of 30-60 minutes. Sleep efficiency of 75%-84% was identified, measuring the time spent in bed before falling asleep and the total sleep duration. Sleep disturbances were reported with scores of 10-18 by 51.2% of participants, and 43.9% consumed sleep medication once a week. Daytime dysfunction was scored at 1-2 by 41.5% of patients, who reported feeling drowsy 1-2 times during daytime activities and exhibited low to moderate enthusiasm while engaging in activities. In conclusion, poor sleep quality was observed among cancer patients undergoing chemotherapy.